2016
DOI: 10.3389/fnana.2016.00064
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Protease-Activated Receptor 1 Does not Affect Dendritic Homeostasis of Cultured Mouse Dentate Granule Cells

Abstract: Protease-activated receptors (PARs) are widely expressed in the central nervous system (CNS). While a firm link between PAR1-activation and functional synaptic and intrinsic neuronal properties exists, studies on the role of PAR1 in neural structural plasticity are scarce. The physiological function of PAR1 in the brain remains not well understood. We here sought to determine whether prolonged pharmacologic PAR1-inhibition affects dendritic morphologies of hippocampal neurons. To address this question we emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Previous research revealed that in vitro entorhinal cortex lesion (ECL) of mouse organotypic entorhino-hippocampal slice cultures induced homeostatic synaptic plasticity of excitatory synapses on dentate granule cells (Vlachos et al, 2012;Lenz et al, 2019). These functional changes depended on cytokine signaling (Becker et al, 2015) and involved the structural remodeling of denervated dendrites (Vlachos et al, 2012(Vlachos et al, , 2013bSchuldt et al, 2016;Willems et al, 2016;Bissen et al, 2021), similar to what is observed after in vivo ECL (Vuksic et al, 2011). Moreover, the induction of homeostatic synaptic plasticity was demonstrated to affect the postlesional recovery of dendritic spine numbers (Vlachos et al, 2013b).…”
Section: Open Access Edited Bymentioning
confidence: 82%
“…Previous research revealed that in vitro entorhinal cortex lesion (ECL) of mouse organotypic entorhino-hippocampal slice cultures induced homeostatic synaptic plasticity of excitatory synapses on dentate granule cells (Vlachos et al, 2012;Lenz et al, 2019). These functional changes depended on cytokine signaling (Becker et al, 2015) and involved the structural remodeling of denervated dendrites (Vlachos et al, 2012(Vlachos et al, , 2013bSchuldt et al, 2016;Willems et al, 2016;Bissen et al, 2021), similar to what is observed after in vivo ECL (Vuksic et al, 2011). Moreover, the induction of homeostatic synaptic plasticity was demonstrated to affect the postlesional recovery of dendritic spine numbers (Vlachos et al, 2013b).…”
Section: Open Access Edited Bymentioning
confidence: 82%
“…For example low concentrations of thrombin, or a specific PAR1-agonist, improve the ability of neurons to express synaptic plasticity without inducing LTP per se ( Maggio et al, 2013b , 2014 ). Thus, while in a recent study we were not able to detect adverse effects of prolonged PAR1-inhibition on dendritic plasticity of neurons ( Schuldt et al, 2016 ), it is conceivable that pharmacological inhibition of PAR1 may not only exert positive effects on neural plasticity.…”
Section: Discussionmentioning
confidence: 56%
“…These and other studies indicate that PAR1 inhibition is beneficial in individuals with neuronal diseases associated with breakdown of the blood-brain barrier and/or increased PAR1 activity [74]. Importantly, long-term PAR1 inhibition has no effect on the physiological neuronal function in vitro [75], implying that PAR1 inhibition in the absence of neurological disease is non-toxic. This finding is of clinical relevance considering the advent of small molecule PAR-modulating drugs in clinical use.…”
Section: Homeostatic Function Of Par Signaling In the Central Nervousmentioning
confidence: 60%